Emerging technologies for semantic work environments techniques, methods and applications - Rech 1968-; Decker; Ras (Information Science Reference, 2008)
\"This book describes an overview of the emerging field of Semantic Work Environments by combining various research studies and underlining the similarities between different processes, issues and approaches in order to provide the reader with techniques, methods, and applications of the study"--Provided by publisher.